2015
DOI: 10.1007/s10068-015-0129-5
|View full text |Cite
|
Sign up to set email alerts
|

Application of slightly acidic electrolyzed water and ultrasound for microbial decontamination of kashk

Abstract: Application of slightly acidic electrolyzed water (SAEW) in combination with ultrasound for decontamination of kashk was investigated. SAEW had a pH of 5.3-5.5, an oxidation reduction potential of 545-600 mV, and an available chlorine concentration of 20-22 mg/L. Kashk is a dairy product with a unique aroma and a high nutritive value produced in Iran. A 2/1 SAEW/kashk ratio showed 1.42, 1.13, 1.24, and 1.37 log CFU/mL microbial reductions in Staphylococcus aureus, Bacillus cereus, Escherichia coli, and Aspergi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 26 publications
(48 reference statements)
1
8
0
Order By: Relevance
“…ese results suggested that the synergistic effect of US combined with SAEW was also related to ultrasonic frequency and microbial species. In addition, SAEW combined with US treatment also significantly improved the reductions in the populations of inoculated S. aureus, B. cereus, E. coli O157 : H7, and A. fumigatus in kashk compared to SAEW alone [20]. In the present study, US and SAEW treatment exhibited the synergistic effect in sterilization of E. coli and presented the highest reduction of E. coli with value of 3.64 log CFU/mL.…”
Section: Effect Of Us Combined With Saew Treatment On the Microbicidasupporting
confidence: 59%
“…ese results suggested that the synergistic effect of US combined with SAEW was also related to ultrasonic frequency and microbial species. In addition, SAEW combined with US treatment also significantly improved the reductions in the populations of inoculated S. aureus, B. cereus, E. coli O157 : H7, and A. fumigatus in kashk compared to SAEW alone [20]. In the present study, US and SAEW treatment exhibited the synergistic effect in sterilization of E. coli and presented the highest reduction of E. coli with value of 3.64 log CFU/mL.…”
Section: Effect Of Us Combined With Saew Treatment On the Microbicidasupporting
confidence: 59%
“…The efficacy of several chlorine‐based disinfectants against vegetative cells and spores of Bacillus spp. has been recently considered by several authors (Nam et al., ; Forghani et al., ). High doses and long contact times are usually required to completely inactivate Bacillus spp.…”
Section: Assessmentmentioning
confidence: 99%
“…The cleaning effect can be even more effective when electrolyzed water and ultrasound are used together. [44][45][46] Li et al, 47 for example, investigated the inactivation ability of such a combination on Staphylococcus aureus. The results illustrated that the number of S. aureus decreased by 3.7 log(CFU)/g after the combined treatment.…”
Section: Combined Ultrasonic Cleaning With Ozonementioning
confidence: 99%
“…Puligundla et al ., 43 who washed broccoli sprouts with AEW and studied its cleaning effect, found that the best cleaning time was 20 s. AEW could effectively reduce the number of harmful microorganisms in broccoli sprouts, and their quality was not significantly altered after washing with the electrolyzed water. The cleaning effect can be even more effective when electrolyzed water and ultrasound are used together 44–46 . Li et al ., 47 for example, investigated the inactivation ability of such a combination on Staphylococcus aureus .…”
Section: Ultrasonic and Ultrasound‐assisted Cleaning Technologiesmentioning
confidence: 99%